ALT Trends through Childhood and Adolescence Associated with Hepatic Steatosis at 24 Years: A Population-Based UK Cohort Study - Ahlia Sekkarie; Jean A. Welsh; Kate Northstone; Catherine E. Cioffi; Aryeh D. Stein; Janet Figueroa; Usha Ramakrishnan; Miriam B. Vos (Children, 2020)
(1) Background: Alanine aminotransferase (ALT) is used to screen for non-alcoholic fatty liver disease (NAFLD) in children; however, the optimal age to commence screening is not determined. Our objective was to describe whether ALT trends from 9–24 years were associated with hepatic steatosis at 24 years in a population-based UK cohort. (2) Methods: The sample included 1156 participants who were assessed for hepatic steatosis at 24 years and had at least two ALT measurements at 9, 15, 17, and/or 24 years. Controlled attenuation parameter scores were used to assess steatosis (low (<248 dB/m), mild/moderate (248–279 dB/m), severe (>279 dB/m)). Sex-stratified mixed-effects models were constructed to assess the liver enzyme trends by steatosis level. (3) Results: The final sample was 41.4% male and 10.4% had severe steatosis. In both sexes, ALT trends from 9 to 24 years differed in those with low vs. severe steatosis at 24 years (p < 0.001). There was no evidence of differences prior to puberty. At 17 years, the low vs. severe geometric mean ratio (GMR) was 0.69, 95% CI: 0.57–0.85 in males and (0.81, 0.65–1.01) females. At 24 years, the GMR was (0.53, 0.42–0.66) in males and (0.67, 0.54–0.84) females. (4) Conclusions: Higher ALT concentration in adolescence was associated with hepatic steatosis at 24 years. The increased screening of adolescents could strengthen NAFLD prevention and treatment efforts.